Treatment Changes In Intermaxıllary Relatıon Of Class Iı, Dıvısıon 1 Subjects - Mirzen Arat; Ayşegül Köklü; Murat Özbek (Galenos Yayinevi, 1994)
Correlation of changes in various components of the skeletal morphology, including intermaxillary relation, were evaluated in two groups comprising Cı II, div 1 subjects treated by standard Edgewise (n=11) and Begg appliances (n=12). Beside the conventional measurements like SNA, SNB and ANB, alternative variables based on TW-HOR and T-VER reference planes were used. Results revealed that type of treatment is efficient in correlation between changes of various components of skeletal morphology and that different measurements may yield different interpretation of the treatment effects.